Stunting Countermeasures Intervention Model in Remote Areas of Banyuwangi Regency East Java - Mei Lina Fitri Kumalasari; Estri Kusumawati; Moch. Irfan Hadi (State Islamic University of Sunan Ampel, 2023)
Stunting in toddlers becomes a chronic nutritional problem. Factors that cause stunting are maternal nutrition during pregnancy, socioeconomic conditions, infectious diseases in infants, access to health services, reproductive health, sanitation and clean water. This study aims to analyze stunting prevention intervention models in remote areas of Sukamade, Banyuwangi Regency. This study is an analytical observational study with a quantitative approach. Data collection techniques by interview and observation using a questionnaire. The sampling technique used a total sampling with a sample size of 42 toddler households. The analysis technique used is the Structural Equation Models (SEM) equation model, an alternative method of PLS. The final results show that environmental variables have a significant effect on stunting. The latent variable that affects the stunting variable is the environmental variable. It is necessary to create an intervention model that takes into account the need for safe drinking water by maintaining water sources and water quality.